Large-scale production of megakaryocytes from human pluripotent stem cells by chemically defined forward programming - Thomas Moreau (Nature Portfolio, 2016)
Platelets are blood circulating corpuscles generated from megakaryocytes that initiate wound healing. Here, Moreau et al. describe a way of producing large quantities of megakaryocytes from human pluripotent stem cells in the laboratory, moving us a step closer to manufacturing transfusion products.